First principle calculation of the photocurrent in a short carbon nanotube: the effect of an external bias. (10th May 2023) - Zhang, Yan; Chen, Jingzhe
Abstract: We studied the transport properties of a short carbon nanotube between two different metal electrodes. Specifically, the photocurrents under a series of bias voltages are investigated. The calculations are completed within the non-equilibrium Green's function method, where the photon–electron interaction is taken as a perturbation. The rule-of-thumb that a forward bias decreases while a reverse bias increases the photocurrent under the same illumination is verified. The first principle results demonstrate the characteristic of the Franz–Keldysh effect, where the photocurrent response edge shows a clear red-shift trend in electric fields along both axial directions. An obvious Stark splitting is observed when some reverse bias is applied to the system due to the huge field strength. In this short-channel situation, intrinsic nanotube states are strongly hybridized with metal electrode states, which results in dark current leakage and specific features such as a long tail and fluctuations in the photocurrent response.